Бізнес-архітектура банківського сектору: зміст та визначальні параметри формування - Ткаченко, Олександр; Tkachenko, Oleksandr (ЗУНУ, 2023)
Вступ. Банківський сектор належить до однієї з найбільш динамічних сфер економічної системи. Саме тому важливою є проблематика формування ефективної бізнес-архітектури банківського сектору, яка забезпечувала б його фінансову стабільність та сприяла економічному розвитку національної економіки. Мета – обґрунтувати зміст бізнес-архітектури банківського сектору та окреслити фундаментальні чинники її формування. Результати. Окреслено основні маркери, що обумовлюють необхідність забезпечення безперервності функціонування банківського сектору. Визначено складові системи управління безперервністю функціонування банківського сектору. Сформульовано змістовну відмінність понять “бізнес-модель банку”, “стратегія банку” та “бізнес-архітектура банківського сектору”. Узагальнено наукові підходи щодо класифікації бізнес-моделей банків. Подано авторське бачення дворівневого структурування бізнес-моделі банку. Висновки. Доведено, що основними принципами формування сучасного банківського сектору як високоадаптивної системи є його відкритість та самоорганізація, цілеспрямованість, емерджентність, цілісність, надійність, гнучкість і стійкість. Передумовою досягнення вищезазначеного є формування оптимальної бізнес-архітектури яка, своєю чергою, є похідною від взаємодії представлених на ринку бізнес-моделей банків. Обґрунтовано, що в умовах сучасної цифрової трансформації економічного простору важливим є комплексна та багатоаспектна ідентифікація бізнес-моделей банків, яка враховувала б сучасні тренди. Introduction. The banking sector is one of the most dynamic spheres of economic life. That is why the problem of forming an effective business architecture of the banking sector, which would ensure its financial stability and contribute to the economic development of the national economy, is important. The purpose of the article is to substantiate the content of business architecture, based on the specifics of the banking sector, and outline the fundamental factors of its formation. Results. The main markers determining the need to ensure the continuity of the banking sector are outlined. The components of the continuity management system of the banking sector are defined. The substantive difference between the concepts of "bank business model", "bank strategy" and "business architecture of the banking sector" is formulated according to the criterion approach. The scientific position on the classification of business models of banks is summarized. The author's vision of the two-level structuring of the bank's business model is presented. Conclusions. It is proven that the main requirements for the modern banking sector as a highly adaptive system are its openness and self-organization, purposefulness, emergency, integrity, reliability, flexibility and sustainability. The prerequisite for achieving the above is the optimal business architecture of the banking sector, which, in turn, is derived from the interaction of the business models of banks presented on the market. It is substantiated that in the conditions of the modern digital transformation of the economic space, it is important to comprehensively and multi-facetedly identify the business models of banks, which would take into account modern trends.
Business architecture of the banking sector: content and determining parameters of formation
Keywords: банківський сектор; бізнес-модель; бізнес-архітектура; класифікація; banking sector; business model; business architecture; classification